2022
DOI: 10.3389/fmicb.2022.936585
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Modulates the Protective Role of Ginsenoside Compound K Against Sodium Valproate-Induced Hepatotoxicity in Rat

Abstract: This study aimed to investigate the potential role of gut microbiota in the hepatotoxicity of sodium valproate (SVP) and the protective effect of ginsenoside compound K (G-CK) administration against SVP-induced hepatotoxicity in rats. Measurements of 16S rRNA showed that SVP supplementation led to a 140.749- and 248.900-fold increase in the relative abundance of Akkermansia muciniphila (A. muciniphila) and Bifidobacterium pseudolongum (B. pseudolongum), respectively (p < 0.05). The increase in A. mucini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…KEGG could provide molecular biological function of the DEGs at the molecular, cellular and organism levels. [27] The biological pathways are important for understanding the sterilization mechanism of asperbutenolide A against with MRSA and, in the current study, the DEGs were mainly involved in the metabolic pathways of amino acid metabolism, carbon metabolism, membrane transport, etc (Figure 3B). The top five downregulated and up-regulated genes of the amino acid metabolism pathways were argF, arcC1, tdcB, ald, argH and ureB, trpC, ureC, trpD, ureA, respectively (Figure 4).…”
Section: Kegg Classification Analysismentioning
confidence: 71%
“…KEGG could provide molecular biological function of the DEGs at the molecular, cellular and organism levels. [27] The biological pathways are important for understanding the sterilization mechanism of asperbutenolide A against with MRSA and, in the current study, the DEGs were mainly involved in the metabolic pathways of amino acid metabolism, carbon metabolism, membrane transport, etc (Figure 3B). The top five downregulated and up-regulated genes of the amino acid metabolism pathways were argF, arcC1, tdcB, ald, argH and ureB, trpC, ureC, trpD, ureA, respectively (Figure 4).…”
Section: Kegg Classification Analysismentioning
confidence: 71%
“…muciniphila increased after the oral administration of SVP, and there was a strong positive correlation between the relative abundance of A. muciniphila and liver function indicators ALT and AST activities (correlation coefficient >0.78). 15 Because the opposite effects of A. muciniphila under different conditions have been reported, it Oxidative stress is one of the common features of SVP-induced liver injury, 38 and anti-oxidative stress is one of the important mechanisms by which A. muciniphila exerts hepatoprotective effect. 18,20 Oxidative stress results from an imbalance between oxidative and antioxidant effects, and is manifested by elevated levels of total oxidants and oxidation products, as well as reduced levels of endogenous antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the ‘drug‐microbe‐gut‐liver’ model and the interactions of its components is of great significance, and it is becoming a new direction for the exploration of the mechanism of drug‐induced liver injury. Our previous study demonstrated that SVP resulted in a disruption of the gut microbiota's structure with a 140‐fold increase in the relative abundance of faecal Akkermansia muciniphila ( A. muciniphila ) in rats, which was partially ameliorated by ginsenoside compound K, a liver‐protective compound 15 …”
Section: Introductionmentioning
confidence: 99%
“…VPA is a commonly used antiepileptic agent whose induced hepatotoxicity has been identified as the third most common cause of drug-induced liver death by the World Health Organization [88,89]. Zhou et al [90]found that sodium valproate-induced hepatotoxicity was related to gut microbiota dysbiosis.…”
Section: Valproic Acid (Vpa)mentioning
confidence: 99%